Managing security services in heterogenous networks confidentiality, integrity, availability, authentication, and access control - Jeyanthi, N., 1977-; Ma, Kun (Computer scientist); Perumal, Thinagaran; Thandeeswaran, N. (Boca Raton : CRC Press, 2021)
A heterogeneous network is a network which connects computers and other devices with different operating systems, protocols, or access technologies. By definition, managing heterogenous networks is more difficult that homogenous networks. Confidentiality, integrity, availability (CIA) remain the foundation of security. This book sheds light upon security threats, defenses, and remediation on various networking and data processing domains, including wired networks, wireless networks, mobile ad-hoc networks, wireless sensor networks, and social networks through the prisms of confidentiality, integrity, availability, authentication, and access control. The book is broken into different chapters that explore central subjects and themes in the development of the heterogenous networks we see today. The chapters look at: Access control methods in cloud-enabled Internet of Things Secure routing algorithms for mobile ad-hoc networks Building security trust in mobile ad-hoc networks using soft computing methods The use and development of Blockchain technology, with a particular focus on the nonce-free hash generation in Blockchain Password authentication and keystroke biometrics Health care data analytics over Big Data Bluetooth: and its open issues for managing security services in heterogenous networks Managing Security Services in Heterogenous Networks will be a valuable resource for a whole host of undergraduate and postgraduate students studying related topics, as well as career professionals who have to effectively manage heterogenous networks in the workplace.
OCLC-licensed vendor bibliographic record.
Keywords: Computer networks -- Security measures -- Management; Heterogeneous distributed computing systems; COMPUTERS / Networking / Security; COMPUTERS / Security / General